KEBEBASAN BEREKSPRESI TERHADAP PENERAPAN PASAL 27A JO. PASAL 45 UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 1 TAHUN 2024 TENTANG PERUBAHAN KEDUA ATAS UNDANG-UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK PASCA PUTUSAN MAHKAMAH KONSTITUSI - Febrananda, Ilham Bayu Aldian; Astutik, Sri; Subekti, Subekti; Marwiyah, Siti (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The level of digital technology development has changed the pattern of communication in society and opened up a wide space for expression in the public sphere. However, the freedom of expression guaranteed by the 1945 Constitution of the Republic of Indonesia often conflicts with the application of Article 27A in conjunction with Article 45 of Law Number 1 of 2024 concerning Electronic Information and Transactions (ITE Law). This provision is considered to be open to multiple interpretations, potentially leading to criminalisation and causing a negative deterrent effect that reduces public participation in democracy. This study aims to answer the main question: how does the application of this article affect the protection of freedom of expression in Indonesia, and to what extent is it consistent with the principles of legality, proportionality, and human rights standards? The research method uses a normative legal approach with a qualitative design. Data was collected through a literature study of legislation, legal doctrine, court decisions, and academic literature. The analysis was conducted deductively and comparatively to assess the conformity of legal norms with enforcement practices and international standards such as the ICCPR. The results of the study show that the application of Article 27A in conjunction with Article 45 of the ITE Law still causes legal uncertainty and is often used as a repressive instrument. The cases of Jerinx SID, Baiq Nuril, and Muhammad Kace illustrate how this article is used inconsistently, sometimes ignoring the principles of legality and proportionality. These findings confirm that there is a serious gap between the constitutional protection of freedom of expression and law enforcement practices. The conclusion of this study emphasises the need for restrictive interpretation and reformulation of the articles of the ITE Law to be more in line with the principles of a democratic state based on the rule of law. Theoretically, this study enriches the discourse on digital criminal law, while in practical terms, it provides recommendations for policymakers and law enforcement officials to prioritise substantive justice and a restorative justice approach. Further research is needed to explore the empirical practices of officials in implementing Constitutional Court decisions, as well as comparisons with other countries in regulating freedom of expression in the digital space.conflicts.